2012
DOI: 10.1590/s1516-35982012000700018
|View full text |Cite
|
Sign up to set email alerts
|

Herbal extracts in diets for broilers

Abstract: -The objective of this study was to evaluate the effect of feeding herbal extracts for broilers on performance and histology of the intestinal mucosa and its effects on the profiting from the metabolizable energy of experimental diets.For so, two experiments were conducted. In experiment I, the inclusion of different herbal extracts in diets on performance and intestinal histology of broilers was evaluated, and in experiment II, the values of apparent metabolizable energy and metabolizable energy corrected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 14 publications
1
23
0
2
Order By: Relevance
“…Moreover, in the present study, the jejunal crypt depth decreased non-significantly in the treatment groups compared to control. The crypts are responsible for production of enterocytes required for renewal of villi and the more the crypt is demanded in terms of cell renewal, the greater its depth [ 31 ], thus indicating that the villi were not compromised in any way in all the treatment groups fed dandelion leaves and fenugreek seeds either alone or in combination with or without enzyme addition. Furthermore, there was an improvement in the villus height/crypt depth ratio in all the treatment groups which has been regarded as a good indicator of better intestinal health [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the present study, the jejunal crypt depth decreased non-significantly in the treatment groups compared to control. The crypts are responsible for production of enterocytes required for renewal of villi and the more the crypt is demanded in terms of cell renewal, the greater its depth [ 31 ], thus indicating that the villi were not compromised in any way in all the treatment groups fed dandelion leaves and fenugreek seeds either alone or in combination with or without enzyme addition. Furthermore, there was an improvement in the villus height/crypt depth ratio in all the treatment groups which has been regarded as a good indicator of better intestinal health [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is the chance that their residues are found in the tissues, and also by the probable induction of cross-resistance for pathogenic bacteria in humans, which could generate problems related to public health. 1 Today in the European Union only three antibiotics are still permitted as growth promoters (Salinomycin-Na, Flavophospholipol and Avilamycin) and a general ban is foreseen in some years from now, because of the increased occurrence of pathogens resistant against therapeutic antibiotics used in animals and humans. 2 With the restricted use or ban of dietary antimicrobial agents we must explore new ways to improve and protect the health status of farm animals.…”
Section: Introductionmentioning
confidence: 99%
“…These extracts present a mechanism of action based on the alteration of the intestinal microbiota, increased enzyme secretion, improved immune response, morpho-histological maintenance of the gastrointestinal tract and antioxidant activity (Brugalli, 2003;Fascina et al, 2012). Several studies have demonstrated their in vitro effect against pathogens because of antimicrobial, antifungal and anthelmintic activities, in addition to powerful antioxidant effects (Kamel, 2000;Petrolli et al, 2012).…”
Section: Introductionmentioning
confidence: 99%